Ultra wideband antenna with band notch at 5.8 gigahertz using conductive silver coated thin film - Abdul Rani, Mohd. Subri (2014)
Wireless communication technology is a fast developing technology which gives a huge impact on social life nowadays. Currently, thin film is one of the emerging technologies in the recent antenna technology and it has been rapidly adapted into the wireless communication system over these few years. It has attracted major attention to antenna designers due to its major advantage which is very low thickness. This thesis focuses on the design of the Ultra Wideand (UWB) antenna with a band notch at 5.8 GHz using the conventional FR-4 and the thin film as the main materials. The UWB antenna is capable of covering the 3.1-10.6 GHz frequencies, which includes the IEEE 802.11.a WLAN frequency of 5.8 GHz. A Split Ring Resonator/Complimentary Split Ring Resonator (SRR/CSRR) was introduced in the design to achieve band notch at 5.8 GHz and reduce interferences from WLAN applications. The effects of the SRR/CSRR on these UWB antennas are thoroughly analyzed in terms of their placements. The SRR/CSRR can be placed at both outside and inside of the radiating element when FR-4 is used. However, placing the SRR outside the radiating element of the transparent antenna produced a poor notch of only -9.61 dB reading on its reflection coefficient. Meanwhile, implementation of SRR inside the radiating element gave better reflection coefficient of -7.80 dB. The surface losses of AgHT-8 limit the possible position to place the SRR on the transparent antenna. Besides, it also significantly reduces transparent antenna’s gain to -6 dBi. The proposed antenna is a new type of antenna that can be integrated with window glass and used for indoor monitoring system.